The Effects of Type Learning Model Numbered Head Together And Think Pair Share - Siti Rahayu; Ari Suningsih (International Journal of Trends in Mathematics Education Research, 2018)
The aim of this research is to know the difference of the average of mathematics learning outcomes between the students Whose learning using cooperative learning model of type Head Head Together (NHT) Whose learning with the students using Think Pair Share (TPS) on the subject matter of the Circle. The population in this research is the eighth class of the second half of SMP N 1 Adiluwih in the academic year 2017-2018. Sampling was taken by cluster random sampling technique. The research instrument used to Obtain the data in the form of the test while for the data analysis is done normality test and homogeneity test. Since the sample comes from a normal and homogeneous distributed the data then it is continued with t-Test. Result of the data analysis can be concluded that there is difference of the mean result of student learning of mathematics using NHT type cooperative learning models with a mean of mathematics learning result of student using TPS learning models and the mean of student learning result by using cooperative learning model of type NHT is greater than the average mathematics learning outcomes of students taught by using the TPS learning models.